Care For Your Pony - Hearne, Tina.; Rixon, Angela (London : HarperCollins, 1994)
This guide gives advice about how to choose a pony and how best to look after it. The aspects of day-to-day care, such as stabling a pony, feeding, handling and grooming, exercise and health, and first aid are covered.